Rios de Portugal: Comunidades, Processos e Alterações - Verónica Ferreira (Investigação, 2019)
The book Rivers of Portugal: Communities, Processes and Alterations appears in a context in which it is recognized the great importance of rivers for the society and in which there is an intense scientific and technical development on the aquatic ecosystems in Portugal. In 17 chapters written by Portuguese researchers, it was intended to cover the various areas of research linked to rivers. Thus, this book begins with the fundamental physical aspects of rivers: hydrology and sedimentology. Eight chapters follow devoted to aquatic organisms: algae, fungi and bacteria, aquatic and riverine vegetation, invertebrates, fish, amphibians and reptiles, mammals, and birds. The following chapters address human activities that cause major changes in ecosystem quality, ecological monitoring, and restoration of degraded river sectors. The last chapters deal with the last section of a river, before the see, the estuaries, and the final one the thermo-mineral springs, environments closely linked to water courses.